The Alternatively Spliced Isoforms of Key Molecules in the cGAS-STING Signaling Pathway - Liang, Jiaqian; Hong, Ze; Sun, Boyue; Guo, Zhaoxi; Wang, Chen; Zhu, Juanjuan (Frontiers in Immunology, 2021)
Alternative splicing of pre-mRNA increases transcriptome and proteome diversity by generating distinct isoforms that encode functionally diverse proteins, thus affecting many biological processes, including innate immunity. cGAS-STING signaling pathway, whose key molecules also undergo alternative splicing, plays a crucial role in regulating innate immunity. Protein isoforms of key components in the cGAS-STING-TBK1-IRF3 axis have been detected in a variety of species. A chain of evidence showed that these protein isoforms exhibit distinct functions compared to their normal counterparts. The mentioned isoforms act as positive or negative modulators in interferon response via distinct mechanisms. Particularly, we highlight that alternative splicing serves a vital function for the host to avoid the overactivation of the cGAS-STING signaling pathway and that viruses can utilize alternative splicing to resist antiviral response by the host. These findings could provide insights for potential alternative splicing-targeting therapeutic applications.